Enhanching Students’ Reading Comprehension through Learning Cell Technique - Aisyah, Aisyah; Nurjannah, Nunung (Universitas Swadaya Gunung Jati, 2016)
The aim of this research is to find out whether Learning Cell Technique can enhance students reading comprehension or not and to find out the improvement of each indicator of students‟ acheivement. This research was conducted by using Classroom Action Research. The subject of this research is the first year students of English Department of Unswagati Cirebon. The population of this research is 200 students and the sample of this research is 44 students. The technique of colecting the data used test and analyzed by using T-test of non-independent. This research was conducted only one cycle and will be continued to the next cycle. Based on the result of this research shows that (1) Learning Cell technique could enhance students‟ reading comprehension but it was still not significant in the first cycle, the result of Towas 1.789 and ttis 2.015. (2) Learning Cell technique can enhance students‟ reading comprehension for two indicators and two other indicators was still no enhancement.Based on the result of the research, it can be concluded that Learning Cell technique can enhance the students' reading comprehension.